HERMENEUTICS AROUND COVARIANCE MATRIX Case Study for The Subjects in Final Exam at SMKN 14 Jakarta - (NIM 201 05 308), Pratikno
Abstract : This thesis discusses an interpretation (hermeneutics) of parameter in covariance matrix. The discussion begins with a background of problem and meaning of hermeneutics. Later on it discusses the scope of study concerning covariance matrix and the aims which will be achieved to motivate students in learning mathematics To study the meaning of all parameters around covariance matrix, we us linear regression as the principal tool. The parameters that will be studied includes all parameters in covariance matrix, correlation matrix, the inverse of covariance matrix, and the inverse of correlation matrix. The approach used in this thesis is empirical by adjusting the results based on real data. In this case we use the result of school exams and National exams at SMKN 14 Jakarta in academic year 2005/2006 for Accounting Study Program which consist of 114 students for 9 theory tests, 7 practice tests and 5 theory and practice tests.